The impact of environmental conditions on water salinity in the area of the city of Inowrocław (north-central Poland) - Hulisz, Piotr; Pindral, Sylwia; Mendyk, Łukasz; Krawiec, Arkadiusz; Pawlikowska, Kamila (Bulletin of Geography. Physical Geography Series, 2017)
The article presents the influence of natural and anthropogenic factors on the chemical and physical properties of surface and ground waters in the area of the city of Inowrocław. It has been shown that the properties of the waters were most strongly affected by the specific geological structure (the city is located within the Zechstein salt dome) as well as the long-term influence of a salt mine and soda plant. The composition of most analysed samples was dominated by Ca2+, Na+ and Cl- ions. In places of heavy industrial activity, some water parameters were several time higher than permissible values according to Polish standards. It is concluded that, due to the threat to the city’s ground drinking water resources and fertile soils, the surface and ground waters in the area in question require permanent monitoring.